PENGARUH PERENCANAAN PAJAK, PENGHINDARAN PAJAK DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Rukiyanti Rukiyanti; Mulyani Mulyani (JURNAL PUNDI, 2023)
This study aims to determine and examine the effect of tax planning, tax avoidance, and capital structure on firm value. This type of research is quantitative research. The research was conducted on property and real estate companies listed on the Indonesia Stock Exchange from 2017-2021. The population in this study totaled 83 companies. This study uses secondary data. The sampling technique used was purposive sampling to obtain a sample of 15 companies so that the total number of research observations was 60 samples. The analysis technique used is multiple linear regression analysis. The test uses the EVIEWS 9 program. The results show that simultaneously tax planning, tax avoidance, and capital structure affect firm value. Tax planning does not affect firm value, tax avoidance negatif affect firm value and capital structure positif affects firm value.Keywords: Tax Planning, Tax Avoidance, Capital Structure, Firm Value